Increased flux through the hexosamine biosynthetic pathway leads to the induction of acetol-CoA caboxylase gene expression in the heart - Imbriolo, Jamie (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2008.